Pengontrolan Derajat Keasaman (pH) Air Secara Otomatis Pada Kolam Ikan Gurame Menggunakan Metode Fuzzy Mamdani - Dimas Guntoro; Gembong Edhi Setiawan; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Water treatment is the main thing that must be considered when gurame fish culture and the degree of acidity plays a very important role for the health of underwater ecosystems, because if the degree of acidity is not available as needed then it can be toxic to fish. Based on these problems, the need for research related to the automation system to control the value of acidity degree in accordance with the needs of gurame fish. In this research there are 2 sensors namely pH meter SEN0161 sensor and Ultrasonic sensor HC-SR04 with arduino microcontroller using Fuzzy Mamdani method. The Fuzzy Mamdani method was chosen to control the acidity of the water according to the needs of the gurame fish by adding as much water as determined from Fuzzy Mamdani calculation as the center point z. From the results of several tests performed known error percentage reading pH meter SEN0161 is 2,569% and the error percent reading Ultrasonic sensor HC-SR04 is equal to 2,992%. In testing the water acidity control system using Fuzzy Mamdani done 10 times, 80% accuracy with average computation time of 0,693 seconds.